ЎҚИТУВЧИЛАР ФАОЛИЯТИНИНГ ХОРИЖДА ВА ЎЗБЕКИСТОНЛИК ОЛИМЛАР ТОМОНИДАН ЎРГАНИЛИШИ - Даўкеева, А. (SCIENCE and SOCIETY, 2021)
While foreign scholars state in their works the presence of important qualities of a teacher, Uzbek teachers and psychologists have studied and continue to study the teaching profession and its features.
Keywords: pedagogical activity; pedagogical ability; didactic ability; academic ability; perceptual ability; speaking ability; organizational ability